Study of nitrogen containing compounds in a closed recirculating water of an aquaponic system growing tritcum aestivum (wheatgrass) - Umi Nasrah, Mohamad Ismail (2015)
A study of nitrogen containing compound in a closed recirculating system of an aquaponic system by using wheatgrass (triticum aesvitum) was conducted. The important point in this study is related to nitrogen cycle in the aquaponics system, where there are interactions of plant, animals (fish) and bacteria. Nitrogen compounds are an essential nutrient for all forms of life but excessive N inputs lead to eutrophication problems. The main N species in waters are dissolved inorganic N (ammonium, nitrite, and nitrate), dissolved N (the largest fraction is made up of amino acids and peptides and it is often called amino N) and particulate organic (due to small organisms: algae and bacteria), and inorganic N (Burt et al., 1993). The objectives of this research are to understand nutrient cycling (nitrogen cycling in particular), to measure level of ammonia, nitrite, nitrate and five physicochemical parameters value (dissolve oxygen, salinity, total dissolved solid, conductivity and pH) in established aquaponics system and to monitor plant growth parameter such as growth rate and to analyses the concentration of nitrogen compound by using ion chromatography and construct graphs of nutrient levels and plant growth rates. In this research the aquaponics already setup, one of the aquaponics system, the fish must be replaced by NH4C1 in order to gives sufficient amount of NH 3 / NH4 (ammonia). Based on problem statement for this research its shows that water and land resources for agriculture are diminishing and world fisheries are at or past their maximum sustainable yields (Parker 2002). Then improving water quality use by agriculture and food production is critical in order to supply the demand for food in the future, chemical fertilizers from traditional farming discharge pollution leading to eutrophication. Lastly elevated nitrogen and phosphorous levels have been documented to pose negative impacts on aquatic ecosystems by using aquaponic system in future, we can control and recycle the amount of nitrogen produces.